2011
DOI: 10.1016/j.ijrefrig.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation and optimal design of supermarket refrigeration systems with supermarket model “SuperSim”, Part I: Model description and validation

Abstract: Conventional supermarket refrigeration systems are responsible for considerable CO 2 emissions due to high energy consumption and large quantities of refrigerant leakage.In the effort to conserve energy and reduce environmental impacts, an efficient design tool for the analysis, evaluation and comparison of the performance of alternative system designs and controls is required. This paper provides a description of the modelling procedure employed in the supermarket simulation model 'SuperSim' for the simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…The facility managers consulted in this work confirmed that HT and LT refrigeration are common terms used within the industry. There are also examples of this terminology being used in the academic literature [21][22][23][24] .…”
Section: Case Study Buildings and Simulation Inputsmentioning
confidence: 99%
“…The facility managers consulted in this work confirmed that HT and LT refrigeration are common terms used within the industry. There are also examples of this terminology being used in the academic literature [21][22][23][24] .…”
Section: Case Study Buildings and Simulation Inputsmentioning
confidence: 99%
“…• According to [6] the load on a horizontal display case without covers is typically divided so that 75% is due to infiltration of ambient air while the remaining 25% (neglecting radiation) is due to conduction. We adopt this ratio here.…”
Section: B Assumptionsmentioning
confidence: 99%
“…Various software codes are available in the literature, able to simulate both the refrigeration and HVAC systems in supermarkets, which can be employed to perform such evaluations. Among all, we mention here Cybermart (Arias, 2005, Arias andLundqvist, 2005), EnergyPlus (Stovall and Van Baxter, 2010), and SuperSim Tassou, 2011a and2011b). Only Energy Plus is freely available, and can be used for the simulation of systems with some complexity but made of conventional components (Cortella et al, 2011).…”
Section: Introductionmentioning
confidence: 99%